Gambaran Pendidikan Kesehatan Pada Ibu Hamil di Masa Pandemi COVID-19 - Retno Ayu Widiyastuti; Widia Lestari; Erwin (HEALTH CARE: JURNAL KESEHATAN, 2023)
Changes due to the COVID-19 pandemic have a significant impact on pregnant women. Pregnant women need health education to increase knowledge. This study aims to determine the need for health education for pregnant women during the COVID-19 pandemic. This study uses a descriptive survey method with a quantitative approach. The research sample was 100 pregnant women respondents in Pekanbaru City which were taken based on criteria using accidental sampling technique. The analysis used is univariate analysis. There are 100 respondents with the majority of respondents aged 20-35 years (85%), with a high school education level (46%), and the majority of respondents' occupations are housewives (62%), The respondent's gestational age is in the second trimester (62%) and is a multigravida mother (55%), respondents need information related to meeting the nutritional needs of pregnant women in the new normal (73%), where the delivery will be used as a delivery facility (62%) , and choosing the right family planning to use after delivery (67%), the main sources of information for pregnant women in seeking health information during a pandemic are the internet (73%) and midwives (48%). The need for health education varies for each pregnant woman, so there are different preferences in seeking information.